Peran Kantor Urusan Agama dalam Menyikapi Pembebasan Kawin di Bawah Umur dan Syarat Nikah di KUA - Mirna Juwita; Mentari Mentari; Faza Lulu; Tengku Riski Muhammad; Shoufi Ramadhan; Wahyu Maulana; Maya Sari Siregar; Deliana Rambe (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
From the research results, the main problem with the role of the Bureau of Religious Affairs is that there are many exemptions for marriage/early marriage. Early marriage refers to married couples who are underage. That's what it says in the Indonesian law on the admissibility of marriage, the age limit is 16 years old, which was the previous requirement, which is not in the law. "Minor Marriage". Under Indonesia's revised Law No. 16 of 2019, which came into effect on October 15, 2019, religious courts allow men and women to marry at the age of 19.This is the case in many cases of early marriage due to various factors, such as: B. The occurrence of extramarital pregnancy, so that some people have to marry off their children instead of enduring the stigma. Want to get married soon. This is permissible under Islamic religious law, but there are certain restrictions on whether marriage is permitted in national legislation, like the aforementioned law. Keywords: KUA, marriage allocation, early marriage